Iḥyā’ al-Mawāt in the Shāfi‘ī School as a Legal Basis for Indigenous Community Ownership of Their Communal Land (Tanah Ulayat) - bin Jamaludin, Uzair; Ubaidillah, Deden; Amin, Fuad (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2025)
This article analyzes the legal relevance of iḥyā' al-mawāt from the perspective of the Syafii Mazhab and contextualizes it against customary land, considering that both have similar characteristics in terms of the land tenure process. This research is essential to establish the legal force of customary land through the iḥyā' al-mawāt approach from an Islamic law perspective. To achieve this goal, the research method used is content analysis, which is classified as a qualitative method whose analysis is descriptive. Iḥyā al-mawāt is the management of land that is not owned and not utilized by anyone. Through the process of iḥyā' al-mawāt, a person is entitled to land ownership after conducting real management. Customary land is related to the territory that is communally managed by indigenous peoples. The results of the research on iḥyā' al-mawāt in the Shafii Mazhab found some differences with Customary Land in terms of land ownership and territory. Iḥyā' al-mawāt applies to free or formerly managed land that has been abandoned, while communal land relates to customary territories that are communally managed by indigenous peoples. Although there are differences in the aspects of ownership and management, both iḥyā' al-mawāt and customary land have the main similarity of land utilization, as well as land management of both implicating proof of ownership that is legal in state law and Sharia. This research provides theoretical benefits in the form of insight, information, and knowledge about the concept of iḥyā' al-mawāt in the Shafi'i Mazhab as a legal basis for indigenous peoples' ownership of their customary land.